TEACHER STRATEGIES IN CLASS MANAGEMENT TO IMPROVE STUDENT DISCIPLINE IN ELEMENTARY SCHOOL - Rizqi Nur Afifah Afifah; M. Reza Ifnuari (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2022)
This paper aims to convey related actions that teachers can use in managing classes to increase student discipline in elementary school so that it can improve quality in an educational institution. The method used for this work is a literature review, drawing data sources from books, magazines, news portals, and other sources of information that may support this article. The teacher's strategy in class management is one of them, by always seeing student attitudes during the learning process. The teacher must always create a fun class situation regardless of face-to-face or online learning. Teacher class management begins with the planning, configuration, and optimization of various source and equipment sources and equipment for learning that are in class to create effectively and quality learning activities for students. In carrying out the learning process, the teacher must be able to control various information technology to keep learning interesting and not boring especially in the future where learning is carried out by blended learning. If the teacher can properly carry out class management it will increase student discipline.